Produção de lipase por amostras de Aspergillus ssp isoladas do semi-árido do estado de Pernambuco, utilizando meios contendo resíduos agroindustriais. - Lima, Brindize Ferreira de (2014)
Microbial enzymes have been extensively produced and used in various industries for decades. Lipases are a group of enzymes that have extensive biotechnological applications due to its versatility of their properties, substrate specificity and enzymatic activity. The high costs of production of microbial enzymes are mainly due to the means of production and purification processes, thereby encouraging research in search of new producer’s microorganisms and to formulate the most economical medium, using mainly in formulating industrial residues that have a high nutritional value. The Caatinga is a little explored region still exists in microbial diversity and biotechnological potential of these existing microorganisms. Selections of samples of Aspergillus sp named SIS 10, 11,14,15 and 16, isolated from the Caatinga of Pernambuco for production of lipase in solid medium were performed, with the SIS 10 and 16 samples obtained the best results in production of the characteristic halos of 2.2 cm, respectively. Then enzyme production tests were performed through submerged fermentation using 6 different media described in the literature as lipase producers. The experiments were performance is 150 rpm, 28 °C for 144 hours in triplicate. The results showed that the highest enzyme production was obtained in the media 4 in sample SIS 16 sample, obtaining a yield of 2.16 U/mg of lipase. After selecting the best media of production, testing for formulation of alternative means were performed using the following agro-industrial residues: wheat bran, rice bran and oil in frying, substituting olive oil in the middle called control. The experiments occurred during 192 hours, 28oC, 150 rpm, and the results indicated the frying oil as a good producer of enzyme equivalent to 276 U/mL enzyme activity. These studies reveal the high lipolytic production biotechnological potential of fungi isolated from soil of Caatinga of Pernambuco State, besides the reuse of agro-industrial wastes for the production of enzymes, can be a viable alternative for the formulation of new means of production for enzyme biotechnology.